2023
DOI: 10.1111/jdv.19581
|View full text |Cite
|
Sign up to set email alerts
|

Upadacitinib treatment in a real‐world difficult‐to‐treat atopic dermatitis patient cohort

Anne R. Schlösser,
Neill Boeijink,
Jill Olydam
et al.

Abstract: BackgroundUpadacitinib was the first JAK‐1 selective inhibitor registered for the treatment of moderate‐to‐severe atopic dermatitis (AD). Although efficacy and safety have been shown in clinical trials, real‐world data on the use of upadacitinib in patients that have been treated with other immunosuppressants and targeted therapies is limited.ObjectivesTo provide real world evidence on the use of upadacitinib treatment in moderate‐to‐severe atopic dermatitis.MethodsIn this prospective observational single‐cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…(67). One real-world study that included 48 difficult-to-treat atopic dermatitis patients showed that upadacitinib was an effective treatment and 14 case adverse effects were reported, including acne-like eruptions, nausea, and respiratory tract infections (68). Such evidence from the real world once again corroborated our findings.…”
Section: Agreements and Disagreements With Other Studiessupporting
confidence: 85%
“…(67). One real-world study that included 48 difficult-to-treat atopic dermatitis patients showed that upadacitinib was an effective treatment and 14 case adverse effects were reported, including acne-like eruptions, nausea, and respiratory tract infections (68). Such evidence from the real world once again corroborated our findings.…”
Section: Agreements and Disagreements With Other Studiessupporting
confidence: 85%